2019
DOI: 10.1097/ede.0000000000001029
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Fine Particulate Matter and Ovarian Reserve Among Women from a Fertility Clinic

Abstract: Background.-An increasing number of studies have linked air pollution to decreased fertility. Whether this is due to an effect on ovarian reserve is unknown. Method.-Our study included 632 women attending the Massachusetts General Hospital Fertility Center (2004-2015) who had a measured antral follicle count. Validated spatiotemporal models estimated daily particulate matter <2.5 μg/m 3 (PM 2.5) (based on residential address) for the 3 months prior to the antral follicle count. We analyzed associations with Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 18 publications
2
30
1
Order By: Relevance
“…Such pathway enrichment is in agreement with previous epidemiological studies, which confirmed that PM2.5 exposure is significantly associated with ovarian dysfunction, including menstrual disorders, lower reproductive capacity, and declined ovarian reserve. [ 50–52 ] Moreover, Cyp11a , Cyp19a , Cyp17a , and Hsd3b related to hormone synthesis were decreased significantly after exposure to PM2.5 for 4 months, while the expression of Hsd17b7 was markedly increased in PM2.5‐exposed ovaries. It has been reported that HSD17b7 mainly expresses in the corpus luteum, which may contribute to estradiol synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such pathway enrichment is in agreement with previous epidemiological studies, which confirmed that PM2.5 exposure is significantly associated with ovarian dysfunction, including menstrual disorders, lower reproductive capacity, and declined ovarian reserve. [ 50–52 ] Moreover, Cyp11a , Cyp19a , Cyp17a , and Hsd3b related to hormone synthesis were decreased significantly after exposure to PM2.5 for 4 months, while the expression of Hsd17b7 was markedly increased in PM2.5‐exposed ovaries. It has been reported that HSD17b7 mainly expresses in the corpus luteum, which may contribute to estradiol synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 50,51 ] High concentrations of PM2.5 increases the risk of ovarian aging as evidence by significant decrease of antral follicle count, a sonographic marker of ovarian reserve. [ 52 ] Intrauterine exposure to diesel exhaust particles compromises the reproductive capacity of female mice and diminishes ovarian reserve. [ 22 ] Moreover, fuel fine particulate matter contribute to ovarian dysfunction by disturbing hormone synthesis and oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sensitive windows are unclear, it has been suggested environmental exposure within several weeks or months can be critical in AMH-producing follicular pools. A recent study discovered average concentration of PM 2.5 within the prior 3 months is associated with decreased antral follicle count [ 17 ]. A study of young women exposed to systemic chemotherapy agents showed the reduction of AMH occurs as early as in 15 days following the exposure [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental exposure to endocrine disrupting chemicals such as parabens was reported to be negatively associated with ovarian reserve [14]. Recent reports corroborate that exposure to higher levels of PM is associated low ovarian reserve parameters [15][16][17]. However, these findings are limited by the small study population.…”
Section: Introductionmentioning
confidence: 98%